Picoeukaryotic Diversity And Activity in the Northwestern Pacific Ocean Based on rDNA and rRNA High-Throughput Sequencing - Wang, Feipeng; Xie, Yuyuan; Wu, Wenxue; Sun, Ping; Wang, Lei; Huang, Bangqin (Frontiers in Microbiology, 2019)
Picoeukaryotes play an important role in the biogenic element cycle and energy flow in oligotrophic ecosystems. However, their biodiversity and activity are poorly studied in open ocean systems, such as the northwestern Pacific Ocean, which is characterized by a complex hydrological setting. Here, we investigated the diversity and activity of picoeukaryotes in the northwestern Pacific Ocean using high-throughput sequencing targeting the V9 region of 18S rDNA and rRNA. Our results showed that the DNA picoeukaryotic communities were mainly represented by Mamiellophyceae, MAST, MALV-II, Spirotrichea, Prymnesiophyceae, and MALV-I (69.33% of the total DNA reads), and the RNA communities were dominated by Spirotrichea, Mamiellophyceae, MAST, Pelagophyceae, and MALV-II (67.46% of the total RNA reads). The number of operational taxonomic units (OTUs) was significantly affected by temperature and salinity, and was decreased with the increasing nutrient concentration both in the DNA and RNA surveys. Significant differences were observed in the community composition between DNA-based and RNA-based molecular approaches, and these differences were mainly attributed to Mamiellophyceae, Spirotrichea, and Pelagophyceae. The RNA: DNA ratio was used as a proxy for relative metabolic activity of the individual OTUs. We found that the relative metabolic activities of Mamiellophyceae, Spirotrichea, and Pelagophyceae species in the northwestern Pacific Ocean were highly affected by the nutrient concentration, i.e., the NO3 + NO2 and SiO3 concentration. Overall, our study shed light on picoeukaryotic diversity and distribution in the northwestern Pacific Ocean and revealed the correlation between the diversity, relative metabolic activities of marine picoeukaryotes, and the environmental factors.